2023
DOI: 10.1093/plphys/kiad078
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the genetic basis of heterosis in elite super-hybrid rice

Abstract: Y900 is one of the top hybrid rice (Oryza sativa) varieties, with its yield exceeding 15 t·hm-2. To dissect the mechanism of heterosis, we sequenced the male parent line R900 and female parent line Y58S using long-read and Hi-C technology. High-quality reference genomes of 396.41 Mb and 398.24 Mb were obtained for R900 and Y58S, respectively. Genome-wide variations between the parents were systematically identified, including 1,367,758 SNPs, 299,149 Indels,and 4,757 SVs. The level of variation between Y58S and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…S9). The above phenomenon could be attributed to two factors: 1) Inheritance from parental varieties such as R900, PA64S, Y58S, and R9311, which possess a japonica genetic background 29,67 , and 2) the introduction of the japonica genetic background is attributed to complex gene exchange between the indica and japonica subgroups, as highlighted in previous studies 42,68 . Observation of the heritability of super-hybrid rice and its parents revealed that parental genetic contributions to hybrids in LYP9, Y1, Y2, CY1000, and other super rice predominantly originated from the maternal side.…”
Section: Genetic Background Analysis Reveals Japonica Ancestry In The...mentioning
confidence: 79%
“…S9). The above phenomenon could be attributed to two factors: 1) Inheritance from parental varieties such as R900, PA64S, Y58S, and R9311, which possess a japonica genetic background 29,67 , and 2) the introduction of the japonica genetic background is attributed to complex gene exchange between the indica and japonica subgroups, as highlighted in previous studies 42,68 . Observation of the heritability of super-hybrid rice and its parents revealed that parental genetic contributions to hybrids in LYP9, Y1, Y2, CY1000, and other super rice predominantly originated from the maternal side.…”
Section: Genetic Background Analysis Reveals Japonica Ancestry In The...mentioning
confidence: 79%
“…Such direction‐shifting ASE genes are referred to as genetically overdominant (Shao et al, 2019; Sun et al, 2023). We performed an association study for these five overdominant genes by looking at the salinity stress tolerance of 175 rice core germplasm varieties harboring either allele for each gene, identifying only one amino acid transporter gene, OsAAT30 (LOC_Os04g12499), the haplotypes of which were phenotypically associated with salinity stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…The female parent of CY1000, “GuangXiang24S” (GX24S), is the leading indica thermosensitive genic male sterile line from the Hunan Hybrid Rice Research Center. The male parent “R900” is the most commonly used hybrid restorer line and contains a large proportion of the japonica genome from introgression of the wide‐affinity japonica varieties 02428 and Lunhui 422 (Sun et al, 2023). We performed a multi‐year, multi‐area yield test of CY1000, which showed that the yield exceeded 13.32 tons per hectare (t/ha), across varied latitudes, with the highest yield reaching 17.28 t/ha in the Yunnan region in 2018 (Figure S2A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in gene expression have been linked to heterosis in many plant traits, such as seed germination and plant height in maize (Birdseye et al ., 2021; Wan et al ., 2022), yield in rice (Sun et al ., 2023), and nicotine biosynthesis in Nicotiana tabacum (Tian et al ., 2018). However, such changes in transcriptional programs can (and possibly will) vary in a spatiotemporal scale, resulting in tissue- or condition-specific changes in the strength of heterosis (Ko et al ., 2016; Yang et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%